Status and perspectives of claims data analyses in Germany—A systematic review. Issue 2 (February 2016) - Kreis, Kristine; Neubauer, Sarah; Klora, Mike; Lange, Ansgar; Zeidler, Jan
Highlights: German claims data offer a comprehensive basis for healthcare research. German claims data were increasingly analysed from 2000 to 2014. The review reveal an increasing percentage of international publications. The most common data source was from a single SHI fund. To ensure a high performing health system, all-payer database analyses are required. Abstract: Background: The aim of this article is to evaluate the status, development, and perspectives of German claims data analyses in the international and health political context. Methods: We conducted a comprehensive literature search in PubMed, Scopus, and DIMDI to identify empirical and methodological articles focusing on health insurance claims data studies published between 2000 and 2014. Inclusion criteria were (1) English/German full text articles or chapters in edited books that (2) focused on the claims data of statutory health insurance funds. Findings: In total, 435 articles were included. Over time, the number of claims data studies has increased strongly and the frequency of policy-relevant research types increased. Along with the historical improvement path of claims data in Germany, we observed a rising percentage of international publications and an increase in the average quality of publications. In contrast to the US or Canada where comprehensive databases have been established, the most common data source in this search was data from a single SHI fund, while databases were rarely used. Conclusions: Claims data are an important source of information for healthcare stakeholders, and their use for research purposes has further increased during recent years in Germany. Despite its potential in optimising the health system, we found a lack of German comprehensive all-payer claims databases compared to the US and Canada.